Sudamérica ante las disrupciones geopolíticas globales. Red de Política de Seguridad - Novak, Fabián (2023)
Autores: Enrique Araníbar, Jaime Baeza Freer, Juliano Cortinhas, María Cristina Escudero Illanes, Carmela García Ganoza, Pablo Montenegro, Eduardo Pastrana Buelvas, Diego Pérez Enríquez, Antonio Jorge Ramalho, Michelle Reyes Milk, Diego Vera.